The Availability of the α7-Nicotinic Acetylcholine Receptor in Early Identification of Vulnerable Atherosclerotic Plaques: A Study Using a Novel 18F-Label Radioligand PET - Wang, Dawei; Yao, Yong; Wang, Shuxia; Zhang, Huabei; He, Zuo-Xiang (Frontiers in Bioengineering and Biotechnology, 2021)
α7-nicotinic acetylcholine receptor (α7nAChR) is an important target for identifying vulnerable atherosclerotic plaques. Previously, we successfully designed and synthesized a series of 18F-labelled PET molecular probes targeting α7nAChR, which are mainly used in the diagnosis of Alzheimer's disease. Based on the characteristics of α7nAChR in blood vessels, we have firstly screened for a suitable novel 18F-labelled PET molecular probe ([18F]YLF-DW), with high selectivity for α7nAChR over α4β2nAChR and a good effect for the imaging of atherosclerotic animal models, to effectively identify vulnerable atherosclerotic plaques at an early stage. Meanwhile, we compared it with the "gold standard" pathological examination of atherosclerosis, to verify the reliability of [18F]YLF-DW in early diagnosis of atherosclerosis. The vulnerable atherosclerotic plaques model of ApoE-/-mice was successfully established. Then based on the methods of 3D-QSAR and molecular docking, we designed oxazolo[4,5-b] pyridines and fluorenone compounds, which are targeted at α7nAChR. Through further screening, a novel alpha7 nicotinic acetylcholine receptor radioligand ([18F]YLF-DW) was synthesized and automatically 18F-labelled using a Stynthra RNplus module. Subsequently, we employed [18F]YLF-DW for the targeting of α7nAChR in atherosclerotic plaques and control group, using a micro-PET/CT respectively. After imaging, the mice were sacrificed by air embolism and the carotid arteries taken out for making circular sections. The paraffin embedded specimens were sectioned with 5 μm thickness and stained with oil red. After staining, immunohistochemistry experiment was carried out to verify the effect of micro-PET/CT imaging. The micro-PET/CT imaging successfully identified the vulnerable atherosclerotic plaques in the carotid arteries of ApoE-/-mice; whereas, no signal was observed in normal control mice. In addition, compared with the traditional imaging agent [18F]FDG, [18F]YLF-DW had a significant effect on the early plaques imaging of carotid atherosclerosis. The results of oil red staining and immunohistochemistry also showed early formations of carotid plaques in ApoE-/-mice and provided pathological bases for the evaluation of imaging effect.